PENOLAKAN DISPENSASI NIKAH OLEH MAJELIS HAKIM PENGADILAN AGAMA KOTA MADIUN (ANALISIS TERHADAP PENETAPAN PERKARA NO.9/Pdt.P/2022/PA.Mn) - Muhammad Ali Murtadlo; Muhammad Fikri Hakim (JURNAL LEGISIA, 2023)
There is a topic on the issue of Marriage Dispensation in the Religious Court of Madiun City, where Mr. Slamet Riyadi bin Sareh as the Petitioner intends to marry his biological son named Ferdyan Ardyansyah aged 17 (seventeen) years from Madiun with a woman named Aprilia Nur Handayani aged 15 (fifteen) years from Sragen. The Petitioner has registered his child's marriage with the Taman District Religious Affairs Office (KUA) based on letter Number B-103/Kua.13.28.3/PW.01/12/2021 dated December 14, 2021. However, the Head of KUA refused on the grounds that the Petitioner's child was still alive. under the age of 19 (nineteen) years.The purpose of this study was to analyze the Determination of Case No. 9/Pdt.P/2022/PA.Mn as well as knowing how the judges of the Religious Courts of Madiun City considered the rejection of the marriage dispensation. Data was collected through document studies and interviews, and data analysis methods were carried out using descriptive analysis methods.The conclusion of this article is that the judge rejected the applicant's marriage dispensation application, due to the lack of sufficient evidence and witnesses who did not support the applicant's strong reason for marrying his child.